Evaluasi Kinerja Pemerintah Desa Terhadap Kualitas Pelayanan di Desa Afdeling 1 Kecamatan Bilah Barat Kabupaten Labuhanbatu - Dwito Novriansyah; Walid Musthafa Sembiring (Penerbit Jurnal Indonesia, 2025)
This study aims to illuminate the performance of the Village Government of Afdeling 1, Bilah Barat District, Labuhanbatu Regency in providing public services to the community. Using a qualitative descriptive approach, data were obtained through library research, observation, in-depth interviews, and documentation. The evaluation was carried out using 5 performance indicators according to Dwiyanto (2002:48-49) as a benchmark in explaining the quality of performance in the Village of Afdeling 1, Bilah Barat District, Labuhanbatu Regency, including productivity, service quality, responsiveness, responsibility, and accountability. The results of the study indicate that the performance of the village government has not been optimal. The productivity and discipline of the apparatus are still low, the quality of service has not met community expectations, and responsiveness to community aspirations is weak. Employee responsibility has not been fully implemented optimally, and accountability, although it already exists, still requires improvement, especially in terms of coordination and service commitment. Several inhibiting factors found include low discipline, limited mastery of technology, minimal infrastructure, weak communication, low work motivation, and less responsive leadership. This study recommends the need for a comprehensive overhaul of the work system, increasing human resource capacity, and improving village governance so that public services can run effectively, efficiently, and accountably